2004
DOI: 10.1021/nl048435y
|View full text |Cite
|
Sign up to set email alerts
|

Percolation in Transparent and Conducting Carbon Nanotube Networks

Abstract: Ultrathin, uniform single-walled carbon nanotube networks of varying densities have been fabricated at room temperature by a vacuum filtration method. Measurements of the sheet conductance as a function of nanotube network density show 2D percolation behavior. In addition, the network transparency in the visible spectral range was examined and the results are in agreement with a standard thin-film model: fits to the standard theory indicate σ ac ) σ dc for transmission measurements at 550 nm. Transmission meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
1,030
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,061 publications
(1,069 citation statements)
references
References 31 publications
38
1,030
0
1
Order By: Relevance
“…In the special case of a metallic thin film (film thickness much smaller than wavelength of light) in air, the electro-optical properties can be modeled as 13,43,44 …”
Section: Resultsmentioning
confidence: 99%
“…In the special case of a metallic thin film (film thickness much smaller than wavelength of light) in air, the electro-optical properties can be modeled as 13,43,44 …”
Section: Resultsmentioning
confidence: 99%
“…where σ dc and σ op are the DC and optical conductivities, respectively; Z o is the impedance of free space (377 ) [37][38][39]. For a system that obeys this relation, a plot of the left-hand side vs. Z o /2R s will result in a straight line, the slope of which is the dimensionless ratio σ op /σ dc .…”
Section: Resultsmentioning
confidence: 99%
“…As previously mentioned, experimental studies have found a direct relationship between the volume of solution deposited and the volume fraction of the resulting network [5]. Figure 3 shows the relationship between the volume fraction and the total number of rods randomly distributed in the film.…”
Section: Resultsmentioning
confidence: 70%
“…The density of a specific CNT film can also be expressed in terms of its volumetric fraction occupied by nanotubes. The volume fraction of a typical laboratory produced nanotube film is related to the volume of CNT solution used for deposition [5,6], and can be directly measured. In a computer simulation, the volume fraction depends on the total number of rods distributed inside the box, and is calculated directly for each configuration generated.…”
Section: Random Network Of Finite Rodsmentioning
confidence: 99%